Influência do projeto acerto na recuperação pós-operatória em artroplastia total de quadril : estudo randomizado - Alito, Miguel Aprelino (2014)
Introduction: Multimodal protocols, when used, enhance several perioperative clinical variables. Limited information is available about the reduction of preoperative fasting with administration of clear liquids enriched with carbohydrate and immunomodulators in orthopedic surgeries. The ACERTO (Accelerated Postoperative Total Recovery) is based on an existing European program (ERAS) and based on the paradigm of evidence-based medicine. It is an educational program. Objectives: To evaluate clinical, biochemical inflammatory variables and safety of the method, shortening up the fast with drink containing carbohydrates and use of immunomodulatory diet in patients undergoing surgery for total hip arthroplasty using cementless technique on the femur and the acetabulum without cement (total hip arthroplasty hybrid type). Methods: A prospective study of 32 patients (16 males, with a mean age of 58 years ranging de 26 to 85 years) were randomized into two groups: 17 patients (Group ACERTO) undergoing abbreviated to offer 12,5% maltodextrin fasting, 2h before induction of anesthesia and use of immunomodulatory diet for five days prior to surgery; 15 patients (Group CONTROL) fasted for 8 hours without preoperative nutritional therapy. Clinically aspiration during induction of anesthesia and hospitalization time and in laboratory tests the levels of hemoglobin (Hb), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) preoperatively and 48 hours postoperatively were evaluated. Results: There were no deaths, infections, dislocations of the prosthesis, reoperation, or blood transfusions. No cases of aspiration occurred during anesthetic induction. Group ACERTO patients had, on average, two days less hospitalization (P < 0,01). Results of hemoglobin did not differ among groups in preoperative and postoperative. VHS values remained similar between groups postoperatively (p = 0,09), but CRP was higher in the control group postoperatively (p = 0,01). Conclusion: Preoperative fasting abbreviation with of carbohydrates in total hip arthroplasty is safe and may be practiced. The protocol investigated as a whole, decreased hospital stay and CRP levels postoperatively.